Determinants of non-adherence to the medications in patients with dyslipidemia: a systematic review - João Filipe Morais Lopes (2021)
Introduction: Dyslipidemia is a major cardiovascular risk factor. Lowering blood lipids reduces cardiovascular events. Many patients need some medication to achieve ideal targets. Non-adherence to medications causes a reduction of their effectiveness. It is a complex problem, which demands for specific answers. The aim of this study is to identify the determinants of non-adherence to medications in patients with dyslipidemia. Methods: We conducted a systematic review. Pubmed and Scopus databases were searched for original articles, published between 2000-2020, using the MeSH terms "Dyslipidemias" and "Medication Adherence". Results: From the initial 3502 identified articles, we selected 46 to include in the final qualitative synthesis. The determinants associated with increased non-adherence were lower age (≤ 50 years), females, African American ethnicity, smoking habits, being a new user of lipid lowering medications, reporting or having concerns about lipid lowering medication side effects and some comorbidities (chronic obstructive pulmonary disease, Alzheimer's disease/dementia, depression and diabetes). On the contrary, adherence is higher in older patients, alcohol drinking habits, taking ß-blockers, having a higher number of comorbidities, having a history of cardiovascular events, cardiac interventions or revascularization procedures, having health insurance and having more provider follow-up visits. Conclusion: There are important identifiable determinants of non-adherence in patients with dyslipidemia. These patients benefit from a specific approach to minimize the problem and maximize the potential benefit of the prescription.